Persepsi Pekerja Perempuan terhadap Praktik Diskriminasi Gender (Studi pada Industri Garmen, Kabupaten Semarang, Jawa Tengah) - Wardany, Sevira Risma; Dewi, Yustina Ertie Pravitasmara (Modus, 2025)
Gender inequality triggers a conflict called gender discrimination. In the world of work with its diverse human resources, gender discrimination still often occurs. The majority of cases make female workers as victims. This study aims to explore the perceptions of female workers who work in several garment industries, Semarang Regency, Central Java related to gender discrimination. Exploring perceptions is carried out starting from investigating triggers, knowing the form, and identifying the impact of gender discrimination experienced by female workers. The method used is qualitative with a phenomenological approach. The data used is primary data collected through non-participatory observation and structured and in-depth interviews with female workers who became informants. The results found that the most important trigger of gender discrimination is patriarchy, with the most obvious form being sexual harassment, which has an impact on work stress on female workers who are victims. Keywords: gender; gender inequality; gender discrimination; women workers. Ketidaksetaraan gender memicu sebuah konflik yang disebut diskriminasi gender. Dalam dunia kerja dengan keberagaman sumber daya manusianya, diskriminasi gender masih kerap terjadi. Mayoritas kasus menjadikan pekerja perempuan sebagai korban. Penelitian ini bertujuan untuk menggali persepsi pekerja perempuan yang bekerja pada beberapa industri garmen, Kabupaten Semarang, Jawa Tengah terkait diskriminasi gender. Penggalian persepsi dilakukan mulai dari menginvestigasi pemicu, mengetahui bentuk, serta mengidentifikasi dampak diskriminasi gender yang dialami oleh pekerja perempuan. Metode yang digunakan adalah kualitatif dengan pendekatan fenomenologi. Data yang digunakan merupakan data primer yang dikumpulkan melalui observasi non-partisipatif serta wawancara terstruktur dan mendalam kepada pekerja perempuan yang menjadi informan. Hasil penelitian menemukan bahwa pemicu diskriminasi gender paling utama ialah patriarki, dengan bentuk paling nyata yaitu pelecehan seksual dan membawa dampak stres kerja pada pekerja perempuan sebagai korban. Kata kunci: gender; ketidaksetaraan gender; diskriminasi gender; pekerja perempuan.